Integrated design of DC-DC power converters target for fast load transient applications - Jia, Meng (2019)
Nowadays, highly integrated electronic products are becoming part and parcel of our daily life. With the technology improvement in Integrated Circuit (IC), more complicated functions can be incorporated into very large-scale systems, rendering the electronic products more powerful and entertaining. The increasing IC size and function blocks bring in new design challenges for its power management circuits, such as accuracy, efficiency, response speed, input and output voltage ranges, and driving capability. The State-of-the-art DC-DC regulators usually combine several control methods in order to fulfill all of the above-mentioned specifications. For instance, a dual mode DC-DC converter applies the Pulse-Width-Modulation (PWM) control method at heavy load condition and shifts to Pulse-Frequency-Modulation(PFM) control at light load condition. This hybrid dual mode operation can indeed improve the efficiency over a wide loading range. However, dual mode operation also implies more complicated circuits design and increased fabrication cost. Apart from it, uncontrolled switching frequency under PFM condition will cause unwanted Electron-Magnetic interference(EMI) issues and challenges of input filter design. Under PWM condition, a power-hungry error amplifier is generally required which will limit the transient response speed. Considering the existing drawbacks of conventional control methodologies and the future development of modern Power Management Units(PMU), several control methods were proposed in this thesis to improve the performances of switching-inductor based DC-DC converters targeting for different specifications. In the beginning, a PWM DC-DC converter works in Discontinues-Conduction-Mode a(DCM) at light load condition was conducted in my research. With a novel Zero-VoltageDetector (ZVD) implemented in this regulator, fast sensing and quick comparison were realized in order to avoid inverse conduction of inductor current. The time delay of ZVD sensing and comparing activities were only about 6ns, and a power conversion efficiency >85% was achieved over a loading range from 10mA to 250mA. Subsequently, in order to be compatible with the development of modern DC-DC regulators, the conventional control methods based on linear control mechanism may not be the best options when dealing with frequently switched loadings. Take this limitation into concern, two designs of high-speed converters with hysteretic non-linear control mechanisms were proposed and conducted. Particularly, switching frequency locking properties were introduced into these two converters with a frequency locking range about several MHz. This hysteretic control method with frequency locking ability is called fixed switching frequency hysteretic control. The proposed designs were fabricated using 0.18mm CMOS process, and their switching frequencies were maintained at 10MHz with less than ±1% variations. The transient recovery time of Design I is about 2ms, and it is only about 0.3ms for Design II. A peak power efficiency of 91% was achieved over a loading range from 100mA to 600mA. Compared to conventional hysteretic PFM controls, the proposed designs have a fixed switching frequency, so the electromagnetic interference (EMI) problems can be greatly reduced and the challenges on input filter design can be minimized. Furthermore, the proposed fixed frequency hysteretic non-linear control topologies can be further used for multi-phase interleaved DC-DC converters applications to provide large current drive capabilities. bIn this thesis, the background information about DC-DC regulators was introduced, and then the motivations and objectives to conduct this research were inspired. Retrieving and analyzing existing technologies, the above mentioned three designs were fully discussed from conceptual ideas, followed by circuits implementations, and all the way to system simulations and measurements. Both advantages and disadvantages will be presented for further study.